RESEARCH OF THE POSSIBILITY OF TRANSMISSION OF LIQUEFIED NATURAL GAS THROUGH A PIPELINE BY A NON-PRESSURE METHOD - Zhmakin, Vitaliy; Budnikov, Victor (Journal of Applied Engineering Science, 2021)
This article discusses the problems of transmission of liquefied natural gas through a non-pressure pipeline from a stationary storage facility to a transport cryogenic tank and ways to solve them. Theoretical studies have been carried out, including mathematical modeling of thermal and hydrodynamic processes during the transmission of liquefied natural gas through a pipeline by a non-pressure method.
Keywords: liquefied natural gas, gas supply, cryogenic liquid, isothermal tank, methane tanker, cryogenic pipeline, two-phase flow, vapor content, saturation temperature, saturated vapor pressure